A nontyphoidal Salmonella serovar domestication accompanying enhanced niche adaptation - Li, Yan; Teng, Lin; Xu, Xuebin; Li, Xiaomeng; Peng, Xianqi; Zhou, Xiao; Du, Jiaxin; Tang, Yanting; Jiang, Zhijie; Wang, Zining; Jia, Chenghao; Müller, Anja; et al. (EMBO molecular medicine, 2022)
Invasive nontyphoidal Salmonella (iNTS) causes extraintestinal infections with ~15% case fatality in many countries. However, the mechanism by which iNTS emerged in China remains unaddressed. We conducted clinical investigations of iNTS infection with recurrent treatment failure, caused by underreported Salmonella enterica serovar Livingstone (SL). Genomic epidemiology demonstrated five clades in the SL population and suggested that the international animal feed trade was a likely vehicle for their introduction into China, as evidenced by multiple independent transmission incidents. Importantly, isolates from Clade‐5‐I‐a/b, predominant in China, showed an invasive nature in mice, chicken and zebrafish infection models. The antimicrobial susceptibility testing revealed most isolates (> 96%) in China are multidrug‐resistant (MDR). Overall, we offer exploiting genomics in uncovering international transmission led by the animal feed trade and highlight an emerging hypervirulent clade with increased resistance to frontline antibiotics. Synopsis The recent increase of human infections caused by invasive non‐typhoidal Salmonella , including Salmonella Livingstone, suggests their evolution towards niche adaptation to humans. This study reveals two novel subclades of S . Livingstone linked to human infections and mainly emerged in China. Genomic epidemiology showed imported animal feed was a major source of the early identified S . Livingstone in China, indicating international feed trading is a transmission route of this pathogen. Phylogeny of global Salmonella Livingstone isolates revealed five major clades of this pathogen, and clinical isolates from China largely belong to Clade‐5. Variabilities of stress responses were observed among isolates from distinct phylogenetic clades, with enhanced resistance to desiccation and diminished tolerance to oxidative stress for Clade‐5 isolates. Two novel subclades of Clade‐5 (i.e., C‐5‐I‐a/b) emerged in the last two decades and predominantly occurred in China accompanying the accumulation of antimicrobial resistance genes. The emerging clades showed significantly increased virulence in distinct animal models. i.e., chicken embryo, zebrafish embryo, and mice, indicating they have been undergoing evolution to adapt to humans. Graphical Abstract The recent increase of human infections caused by invasive non‐typhoidal Salmonella , including Salmonella Livingstone, suggests their evolution towards niche adaptation to humans. This study reveals two novel subclades of S . Livingstone linked to human infections and mainly emerged in China.